Designing a system with machine learning to formative research projects management. Issue 1 (June 2021) - Pineda, C.; Morales, A.; Lopez, L.; Benitez, C.; Sanchez, S.
Abstract: Artificial intelligence is marked among emerging technologies and is one of the most projected expectations for future dates. In the last decade this technology has been implemented in various sectors, without leaving the education and research sector, generating positive results. Among the most demanded algorithms are machine learning, because it gives the ability to "learn" to machines and information systems through experience and not rely only on data from system inputs in a given context. For this reason and also because of the difficulty that students and teachers express in the elaboration of training research documents, the objective of this research is to design a system that assists the user in the construction of the different sections of a formative research project. The research is descriptive and technological development. Among the results found is the behavior of the proposed system and identifies the different technologies to be used for future development. It is concluded that the system is structured by the MVC(Model View-Controller) architectural pattern which facilitates the scalability and maintenance of the system in the future, in addition to the implementation of the libraries of Python, NLTK(Natural Language Toolkit), Scikit-learn, Tensor Flow and Keras, allow the system to fully use machine learning for scientific and academic text prediction.